Hi everyone,

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

2 posts
• Page **1** of **1**

Hi everyone,

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

- qwertytam
**Posts:**1**Joined:**Tue Nov 27, 2012 1:15 am

qwertytam wrote:I need to rearrange this formula so that it is in terms of M

u = A / (M x S)

L = u^[(2(M + 1))^0.5] / (1 - u)

I think this turns into this:

I dont think this can be solved for M.

- FWT
**Posts:**92**Joined:**Sat Feb 28, 2009 8:53 pm

2 posts
• Page **1** of **1**